Intra-abdominal cystic lymphangioma in adults: A case series of 32 patients and literature review. (September 2022) - Maghrebi, Houcine; Yakoubi, Chaima; Beji, Hazem; Letaief, Feryel; Megdich, Sadok; Makni, Amin; Boukriba, Seif; Frikha, Wassim; Ayadi, Mouna; Kacem, Montasser
Abstract: Introduction: Cystic lymphangioma (CL) is a benign tumor originating from the lymph vessels. Lymphangiomas in the abdominal cavity are extremely rare, particularly in adults. This article was designed to study the epidemiological, diagnostic difficulties, and therapeutic principles of intra-abdominal cystic lymphangioma (ACL) in adults. Material and methods: We conducted a single-center, retrospective study of 32 adult patients with ACL admitted to surgical department "A" in "La Rabta Hospital" in Tunis, from January 1998 through December 2020. The demographic, clinical, biological, radiological characteristics, histopathologic, and therapeutic data were collected, as well as the surgical intervention used and the postoperative immediate and late complications. Results: Thirty-two adult patients with ACL were recruited, including 20 females and 12 males. The median age at treatment was 47 (range 14–80) years. The most prevalent sites were the retroperitoneum (25%), the mesentery (21.9%), and the paracolic gutters (n = 18. 7%). Twenty patients underwent open surgery (62.5%), whereas 12 cases (37.5%) had laparoscopic surgery. Twenty-eight patients received total cystectomy (87%). Three recurrences were observed during follow-up (9.4%). Conclusion: The clinical features of CL in adults remain unclear. The diagnosis is only confirmed by histopathological examination after complete surgical resection. The laparoscopic approach is considered safe and feasible. Highlights: Lymphangiomas in the abdominal cavity are extremely rare, particularly in adults. Cystic lymphangioma is a benign tumor originating from the lymph vessels. The clinical presentation is various. Whenever possible, laparoscopic resection should be the treatment of choice. To prevent a recurrence, complete excision is the best option.